Tunable optical low-pass filtering based on chirped grating in arrays of graphene - Yingquan Ao; Xiaoling Chen; Miaomiao Zhao; Hao Ni; Dong Zhong; Fangmei Liu; Xuewen Chen; Junjie Dong; Zhe Liu (PLoS ONE, 2026)
We numerically investigate asymmetric light propagation in chirped gratings with embedded graphene arrays (CG-GA). The structure comprises alternating graphene sheets and dielectric layers, featuring a linearly chirped spatial period. Using the forward transmission matrix method (FTMM), we demonstrate that CG-GA support multimode resonance. The transmittance of resonant modes exhibits a significant wavelength-dependent decay, ultimately reaching a cutoff. This phenomenon indicates the structure functions as a tunable optical low-pass filter, whose transmittance, cutoff wavelength, and bandwidth can be modulated by varying the number of grating periods, the chirped period gradient, and the graphene chemical potential. This study may be utilized for spectral scanning and adaptive optics applications.